2007
DOI: 10.1136/jmg.2007.049981
|View full text |Cite
|
Sign up to set email alerts
|

Cowden syndrome and Bannayan Riley Ruvalcaba syndrome represent one condition with variable expression and age-related penetrance: results of a clinical study of PTEN mutation carriers

Abstract: Careful phenotyping gives further support for the suggestion that BRRS and CS are actually one condition, presenting variably at different ages, as in other tumour-suppressor disorders such as neurofibromatosis type 1. This has important counselling implications, such as advice about cancer surveillance, for children diagnosed with BRRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 56 publications
7
106
0
5
Order By: Relevance
“…Although they both cause hamartomas and several other characteristics, individuals carrying the Cowden syndrome are also prone to elevated cancer risk, in particular cancers of the thyroid and breast. 144 While germline mutations in PIK3CA and AKT3 (the Akt isoform expressed in neural tissue) may cause megalencephaly, 145 a most recent study 146 reported PI3KCA, but also AKT1 germline mutations in some families revealing the Cowden or a Cowden-like syndrome. Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…Although they both cause hamartomas and several other characteristics, individuals carrying the Cowden syndrome are also prone to elevated cancer risk, in particular cancers of the thyroid and breast. 144 While germline mutations in PIK3CA and AKT3 (the Akt isoform expressed in neural tissue) may cause megalencephaly, 145 a most recent study 146 reported PI3KCA, but also AKT1 germline mutations in some families revealing the Cowden or a Cowden-like syndrome. Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…Although the phenotypic features associated with germline PTEN mutation show highly variable penetrance, no consistent genotype-phenotype relationship has been identified. Indeed, the same mutation can cause either Cowden's syndrome or Bannayan-RileyRuvalcada syndrome within the same family (Zori et al, 1998) strongly suggesting that the different PTENmutation disorders are in fact one disease with a broad and highly variable spectrum of clinical features, as is the case with other autosomal dominant tumor suppressor disorders such as neurofibromatosis type I (Lachlan et al, 2007).…”
Section: Germline Mutations Of Pten Cause Neurological Abnormalitiesmentioning
confidence: 99%
“…Most studies have failed to demonstrate a consistent genotype-phenotype relationship between CS and BRRS, but recently, studies have suggested that the unique features in the 2 syndromes may actually represent age-related penetrance of the same condition. 8 People with CS and BRRS within the same family (CS/BRRS overlap families) have been reported. 9 Therefore, early diagnosis of BRRS at a young age may allow patients to be monitored for the onset of malignant disease.…”
mentioning
confidence: 99%